-11(26x-52)=44(-9x+3)

Simple and best practice solution for -11(26x-52)=44(-9x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11(26x-52)=44(-9x+3) equation:


Simplifying
-11(26x + -52) = 44(-9x + 3)

Reorder the terms:
-11(-52 + 26x) = 44(-9x + 3)
(-52 * -11 + 26x * -11) = 44(-9x + 3)
(572 + -286x) = 44(-9x + 3)

Reorder the terms:
572 + -286x = 44(3 + -9x)
572 + -286x = (3 * 44 + -9x * 44)
572 + -286x = (132 + -396x)

Solving
572 + -286x = 132 + -396x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '396x' to each side of the equation.
572 + -286x + 396x = 132 + -396x + 396x

Combine like terms: -286x + 396x = 110x
572 + 110x = 132 + -396x + 396x

Combine like terms: -396x + 396x = 0
572 + 110x = 132 + 0
572 + 110x = 132

Add '-572' to each side of the equation.
572 + -572 + 110x = 132 + -572

Combine like terms: 572 + -572 = 0
0 + 110x = 132 + -572
110x = 132 + -572

Combine like terms: 132 + -572 = -440
110x = -440

Divide each side by '110'.
x = -4

Simplifying
x = -4

See similar equations:

| 6p*3= | | 48/3=x/4 | | 5+3(-2)=-1 | | 30+0.35c=72 | | 3s=3 | | 2.5z=-75 | | 5(2)+3(0)=-1 | | -10t=-8t+10 | | 2.8=2n-5 | | W+3.34=5.64 | | 3x+(k+2)x=1-k | | -9+4d=9+2d | | 16-6(n)=2+n | | 4.8-1.8=0.4y | | -5*-25=25-10*-25 | | 4n^2-35=-4n | | y=43+-10x | | Y-6.8=7.4 | | -4b+4=2 | | y=-10x+43 | | 2x-11=7x+44 | | 83+(-9)=92 | | 10r=5+9r | | 12x^3/18x^6 | | -6y+33=-9(y-5) | | 7h=6h+3 | | 25+0.25p=60 | | X+2y=471 | | 4x-9y+x-5y+2= | | 13(n-2)=-4(11+m)+1 | | 2(y+8)=5y+28 | | 2x^2-6x+6=18-2x+x^2 |

Equations solver categories